2019
DOI: 10.3389/fpsyg.2019.01704
|View full text |Cite
|
Sign up to set email alerts
|

On the Association Between Musical Training, Intelligence and Executive Functions in Adulthood

Abstract: Converging evidence has demonstrated that musical training is associated with improved perceptual and cognitive skills, including executive functions and general intelligence, particularly in childhood. In contrast, in adults the relationship between cognitive performance and musicianship is less clear and seems to be modulated by a number of background factors, such as personality and socio-economic status. Aiming to shed new light on this topic, we administered the Wechsler Adult Intelligence Scale III (WAIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 75 publications
3
40
0
1
Order By: Relevance
“…In older adults, this pattern seems to be confirmed for musicians, with higher performances on long-term visual-spatial memory, working memory, processing speed and verbal fluency (Hanna-Pladdy and MacKay, 2011;Hanna-Pladdy and Gajewski, 2012;Amer et al, 2013;Fauvel et al, 2014;Mansens et al, 2018;Criscuolo et al, 2019;Ferreri et al, 2019). The EEG study of Moussard et al (2016) on elderly musicians (currently practicing about 11 h/week) and non-musicians, confirmed a beneficial effect of musical practice on executive control, and highlighted a more anterior distribution of the P3 wave in musicians, suggesting successful functional reorganization in elderly musicians according to the authors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In older adults, this pattern seems to be confirmed for musicians, with higher performances on long-term visual-spatial memory, working memory, processing speed and verbal fluency (Hanna-Pladdy and MacKay, 2011;Hanna-Pladdy and Gajewski, 2012;Amer et al, 2013;Fauvel et al, 2014;Mansens et al, 2018;Criscuolo et al, 2019;Ferreri et al, 2019). The EEG study of Moussard et al (2016) on elderly musicians (currently practicing about 11 h/week) and non-musicians, confirmed a beneficial effect of musical practice on executive control, and highlighted a more anterior distribution of the P3 wave in musicians, suggesting successful functional reorganization in elderly musicians according to the authors.…”
Section: Discussionmentioning
confidence: 88%
“…Musical practice also influences cognitive functioning, involving better performance on tasks that directly call upon skills explicitly learned during formal music learning ( near transfers ) but also with an effect on general cognitive functions ( far transfers) in musicians ( Fauvel et al, 2013 ; Schellenberg and Weiss, 2013 ; Schlaug, 2015 ). Studies reported better performance for musicians compared to non-musicians mainly in executive functioning, notably working memory, flexibility and verbal fluency ( Degé et al, 2011 ; Criscuolo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, after several months of learning to play a musical instrument, children have shown several improved cognitive functions [ 150 , 151 , 152 , 153 ], such as working memory (especially auditory), inhibitory control, and spatial and logical intelligence. Moreover, professional musicians seem to have higher intelligence quotient (IQ) scores than controls, when all other variables are matched, and in a positive correlation with years of training [ 154 ].…”
Section: Boosting Endogenous Bdnf: Musicmentioning
confidence: 99%
“…Musical training is another important factor that would be a strong predictor of music receptivity. It has been reported that musical training is associated with perceptual and cognitive skills, including executive functions and general intelligence ( Criscuolo et al, 2019 ). We can anticipate higher musical training or musical inclination to be associated with higher music receptivity.…”
Section: Discussionmentioning
confidence: 99%